Sitios de infección por hongos más frecuentes en la zanahoria (Daucus carota L.) y patogenicidad en sus diferentes tejidos. - Rivera, German (1988)
Fungi from carrot roots collected in the field local market were isolated and identified. Sites of natural infection on the root were recorded. Sixteen genera were identified and their pathogenicity tested by  placing them on: not wounded periderm, pericyclic parenchyma, phloem parenchyma and xylem parenchyma. Half of the total fungi was isolated in both field and market samples. The most frequent natural infection sites were the crown, end of the tap root, and lateral roots. In the pathogenicity tests a gradient of resistance was shown varying from a very high level at periderm to a low level at the xylem parenchyma.  Sclerotinia sclerotiorum,  Sclerotium rolfsii, Fusarium tricinctum, F. nivale, F. solani, F. oxysporum, Fusarium sp., Trichoderma sp. y Gliocladium sp., all penetrated directly throught the periderm and also infected the other tissues. Geotrivhum candidum Rhizopus stolonifer . Verticillium sp., Penicillium so., and Candida sp. did no intect the periderm, but were pathogenic  to the pericyclic, phloem, and xylem parenchyma. Phoma sp. and Mucor sp. only infected phloem and xylem parenchyma.